Microbial Status of Groundwater in and Around Cuddalore Town, Tamilnadu - K. Jayachandran, C. Jayanthi, M. Susiladevi, K. Pugazhendy (Recent Research in Science and Technology, 2009)
Water is one of the abundantly available substances in nature. The groundwater is believed to be comparatively clean and free from pollution than surface water. But prolonged discharge of domestic sewage and industrial effluents causes the groundwater to become polluted and create health problems. Coliforms might cause intestinal disorders of the inhabitants and pilgrims. Ground water samples from 15 locations have been collected from Cuddalore Town including SIPCOT industrial area. The present study deals with the analysis of total Coliform count by most probable number (MPN) method and to identify the presence of gram negative or gram positive organisms. The bacteriological quality of groundwater had crossed the upper limits prescribed by WHO. The results found that the water in all these places was found to be unfit for human consumption due to contamination. Pollution control measures and strict enforcement of its laws have been recommended.